Fantasmas trágicos: algunas observaciones sobre su papel, aparición en escena e iconografía - Aguirre Castro, Mercedes (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2006)
This article reconsiders the most significant ghostly appearances in Greek tragedy, emphasizing certain aspects concerning their character and their role in each play. At the same time it aims to point out the relationship between these tragic ghosts and a number of iconographical representations in Attic and South Italian pottery, with the aim of putting forward ideas about how tragic ghosts were conceived and represented on stage. Especially interesting –and the subject of a more detailed study and interpretation– is the image on a Lucanian nestoris connected with the appearance of Clytemestra´s ghost in Eumenides.
Keywords: Ghosts; Tragedy; Theatre; Stage; Iconography; Necromancy